SIX1 Activation Is Involved in Cell Proliferation, Migration, and Anti-inflammation of Acute Ischemia/Reperfusion Injury in Mice - Jin, Yong; Zhang, Manling; Li, Meishuang; Zhang, Hong; Zhao, Lihua; Qian, Cheng; Li, Shensen; Zhang, Hao; Gao, Min; Pan, Binbin; Li, Rongfeng; Wan, Xin; et al. (Frontiers in Molecular Biosciences, 2021)
Nephrogenic proteins are re-expressed after ischemia/reperfusion (I/R) injury; however, the role of these proteins is still unknown. We found that sine oculis homeobox 1 (SIX1), a developmentally regulated homeoprotein, is reactivated in tubular epithelial cells after I/R injury associated with cell proliferation/migration and anti-inflammation. We demonstrated that SIX1 promoted cell proliferation by upregulating cyclin and glycolytic genes and cell migration by increasing the expression of matrix metalloproteinase 9 (MMP9) in the cell model. Notably, SIX1 targeted the promoters of the amino-terminal enhancer of split (AES) and fused in sarcoma (FUS), which are cofactors of nuclear factor-κB (NF-κB) subunit RELA, and then inhibited the transactivation function of RELA. The expression of monocyte chemotactic protein-1 (MCP-1) was decreased by the SIX1-mediated NF-κB pathway. Our results showed that the expression of cyclin, glycolytic genes, and MMP9 were significantly increased, and the infiltration of monocytes/macrophages (Mophs) was suppressed in SIX1 overexpression kidney at 1 day, 2 days, and 3 days after reperfusion. The overexpression of SIX1 resulted in reducing kidney damage from I/R injury in mice by promoting cell proliferation and migration and by inhibiting inflammation. Our study provides evidence that SIX1 involved in cell proliferation, migration, and anti-inflammation in the I/R model, which might be a potential therapeutic target that could be used to ameliorate kidney damage.